Hydrocarbon Potentiality and Depositional Environment of Naokelekan Formation in Binari Serwan-1 Well, NE-Iraq Using Infrared Factors and Palynological Analysis Evidence - Rzger A. Abdula; Maryam I. Abdulla; Nabaz A. Salih; Sazan A. Isa; Hedayat Hashmi (Tikrit Journal of Pure Science, 2020)
The cuttings from the Jurassic Naokelekan Formation have been studied in the oil exploratory Binari-Serwan-1 Well in Dokan Town, Iraqi Kurdistan Region, NE Iraq. Both infrared spectrometry techniques and microscopic study were used for determining hydrocarbon generation potentiality. The prepared strewn slides have been studied under polarizing microscope. The Naokelekan Formation has revealed an excellent total organic carbon (TOC) wt. % content, ranging from 4.20 to 5.88 wt. %. The palynomorphs as well as phytoclasts are totally absent and only the amorphous organic matter (AOM) was identified. The concentrated kerogens of selected samples were analyzed by the Infrared Spectrometer. The results of these samples analysis show existence of kerogen types II and III, which coincides with the microscopic study. This organic matter is of gas and oil prone types. This study suggests that the sediments were deposited in a marine, suboxic to anoxic environment.